The role of culturally-driven strategic agility in enhancing adaptation to sudden changes: Evidence from Saudi projects - Alamri, Reem Abdullah R (Edelweiss Applied Science and Technology, 2025)
This study examines the role of culturally driven strategic agility in enhancing the adaptability of Saudi projects to sudden changes. Drawing on theories of dynamic capabilities and adaptive leadership, the research adopts a mixed-methods approach, combining quantitative data from 265 public and private sector projects with qualitative insights from 20 semi-structured interviews. The findings reveal that advanced information systems and adaptive leadership significantly improve project adaptability in volatile environments. In contrast, dynamic resource reconfiguration remains limited by centralized governance and rigid administrative structures. Organizational and cultural barriers, such as bureaucracy and resistance to change, are found to moderate the relationship between strategic agility and adaptability, often weakening it. Managerial experience plays a pivotal role in fostering adaptive capacity. A comparative analysis with international cases—including Singapore, the UAE, and Germany—highlights the importance of integrating advanced technologies with institutional support. The study concludes that fostering culturally aligned strategic agility is essential for achieving the ambitious transformation goals of Vision 2030 and maintaining high performance in complex and dynamic project settings. These insights offer practical guidance for policymakers and project leaders seeking to build more resilient and responsive project systems in Saudi Arabia.